Peptídeos derivados da toxina ParE: síntese, estrutura e estudos de inibição de DNA topoisomerases - Rocha, Camila Aguiar [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The toxin-antitoxin system ParE-ParD is a bacterial system of post-segregational death encoded in a wide range of hosts. ParE is a small protein of approximately 12 kDa encoded by parE gene. ParD is an antitoxin about 9 kDa, encoded by the parD gene, able of complexing with ParE and neutralize it. Studies have shown the involvement of the enzyme DNA gyrase in the cell death process by ParE, however, is not available in the literature any evidence of inhibition of this protein on the activity of topoisomerase IV. Although found in a wide variety of micro-organisms, the ParE function has not been fully elucidated and its cytotoxic mechanism remains unknown. Based on the primary structure of the E. coli ParE and the limited data available for this toxin, mimetic peptides were rationally designed aiming at understanding the mechanism of inhibition of ParE on the activity of DNA gyrase, as well as on the topoisomerase IV and human topoisomerase II activities. These peptides sequences were synthesized by solid phase methodology, purified and analyzed by high performance liquid chromatography and characterized by mass spectrometry. The ability of these mimetics to inhibit the activity of topoisomerases was tested by electrophoresis on agarose gel. The peptides that showed better results on the inhibition activity of topoisomerases were ParERM3 and ParEC3 , designed to contain the L61-R100 and L69-R100 amino acids sequence, respectively, found of the C-terminal portion of the ParE structure of Escherichia coli. The LNIES sequence (L101 to S105), when present in the mimetic peptides, attenuated the toxicity of the peptides on topoisomerases activity, probably by interfering in the topoisomerase - peptide interactions. Despite the absence of data in the literature regarding the toxicity of ParE protein on the topo IV and human topo II activities, the peptides ParERM3 and ParEC3 showed better inhibitory activity on these enzymes when compared...

O sistema toxina-antitoxina ParE-ParD é um sistema bacteriano de morte póssegregacional codificado numa ampla gama de hospedeiros. ParE é uma proteína pequena, de aproximadamente 12 kDa codificada pelo gene parE. ParD é uma antitoxina de cerca de 9 kDa, codificada pelo gene parD, capaz de complexar com ParE e neutralizá-la. Estudos têm mostrado o envolvimento da enzima DNA girase no processo de morte celular pela ParE, entretanto, não se tem disponível na literatura nenhuma evidência de inibição desta proteína sobre a atividade da topoisomerase IV. Embora encontrada numa ampla diversidade de microorganismos, ParE não possui função celular totalmente elucidada e seu mecanismo de citotoxicidade permanece ainda desconhecido. Com base na estrutura primária da proteína ParE de E. coli e nos escassos dados disponíveis para esta toxina, peptídeos miméticos foram racionalmente projetados visando compreender o mecanismo de inibição de ParE sobre a atividade da DNA girase, bem como, avaliar a ação destes miméticos na atividade da Topoisomerase IV e da Topo II humana. Estas sequências peptídicas foram sintetizadas pela metodologia de fase sólida, purificadas e analisadas por cromatografia líquida de alta eficiência e caracterizadas por espectrometria de massas. A capacidade de inibição destes peptídeos miméticos sobre a atividade das topoisomerases foi testada por ensaios de eletroforese em gel. Os peptídeos que apresentaram melhores resultados de inibição sobre a atividade das topoisomerases foram o ParERM3 e o ParEC3, projetados para conter os resíduos de aminoácidos L61-R100 e L69-R100, respectivamente, presentes na porção C-terminal da estrutura da proteína ParE de Escherichia coli. A sequência “LNIES” (L101 a S105), quando presente nos peptídeos miméticos atenuou a toxicidade dos mesmos frente às topoisomerases, provavelmente por interferir na interação peptídeo-topoisomerase. Embora não existam...
Keywords: Biotecnologia; Peptídeos; Dicroismo circular; Peptides